Thoracoabdominal Normothermic Regional Perfusion for Cardiac Procurement. Issue 10 (19th April 2022) - Joyce, David L.; Carlson, Samuel F.; Kohmoto, Takushi; Durham, Lucian; Ubert, Adam; Candek, Christopher; Koerten, David; Joyce, Lyle D.
Abstract : In donation after circulatory death donors, warm ischemia time is a significant threat to successful cardiac transplantation. The ability to perfuse these organs during the minutes after death, until cardiac evaluation is completed to satisfaction, is crucial in limiting total warm ischemic time. Thoracoabdominal normothermic regional perfusion (TANRP) has emerged as a promising strategy for recovering and monitoring these hearts. We propose a series of clinical practice pearls that we follow for all donation after circulatory death procurements to streamline the process of setting up a TANRP circuit and ensuring all team members present at time procurement are familiar with the procedure. Bicaval cannulation is achieved via the abdomen for aortic cannulation, and via the chest for right atrial cannulation, avoiding deairing maneuvers and providing the shortest possible duration from incision to initiation of cardiopulmonary bypass. Here, we describe a series of practice techniques which we have utilized in our early experience with TANRP.